Phase portraits of Abel quadratic differential systems of second kind with symmetries. Issue 2 (3rd April 2019) - Ferragut, Antoni; García-Saldaña, Johanna D.; Valls, Claudia
ABSTRACT: We provide normal forms and the global phase portraits on the Poincaré disk of the Abel quadratic differential equations of the second kind having a symmetry with respect to an axis or to the origin. Moreover, we also provide the bifurcation diagrams for these global phase portraits.